Los actores sociales y la violencia política en Puno - Rodríguez, Yolanda (1992)
In 1991, political violence constituted one of the main problems in this highland region. Initially focused on two provinces in the north of Puno, political violence has spread significantly in the last three years. This increase is fundamentally due to the growing pressure from Sendero Luminoso to control territorial spaces and open new fronts for the development of the "people's war".